2019
DOI: 10.1007/s10393-019-01453-z
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Pathogen Seroprevalence in Cattle in a Wildlife–Livestock Interface, Kenya

Abstract: A cross-sectional study was conducted to determine the seroprevalence of Brucella spp. and Leptospira spp. and risk factors of exposure in cattle in three zones with varying land use types and wildlife–livestock interactions. Five villages were selected purposively; two in areas with intensive livestock–wildlife interactions (zone 1), another two in areas with moderate livestock–wildlife interactions (zone 2) and one in areas where wildlife–livestock interactions are rarer (zone 3). Sera samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
3
12
2
Order By: Relevance
“…seroprevalence in humans and camels in Kenya 8 , 9 , 13 , while several serological studies have also demonstrated the exposure to Brucella spp. in Narok County 12 , 13 , 17 .
Figure 1 Map of Kenya showing the location of the study areas in Narok and Marsabit.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…seroprevalence in humans and camels in Kenya 8 , 9 , 13 , while several serological studies have also demonstrated the exposure to Brucella spp. in Narok County 12 , 13 , 17 .
Figure 1 Map of Kenya showing the location of the study areas in Narok and Marsabit.
…”
Section: Methodsmentioning
confidence: 99%
“…Brucellosis has been successfully controlled in several developed countries using host species-specific livestock vaccines or test and slaughter policies in animals with no history of vaccination 8 . In Kenya, seroprevalences ranging from 0.1 to 46.5% in humans 9 11 and 1.0–38.0% in livestock have been reported, with higher prevalence recorded in pastoral areas 9 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The herd seroprevalence of brucellosis in cattle farmed at the wildlife-livestock-human interface in East African countries was reported to be 46.7% in Tanzania [ 20 , 21 ], 26.7% [ 22 ] and 68.7% [ 23 ] in Kenya. An increase of 42.0% in herd prevalence from 2017 [ 22 ] to 2019 [ 23 ] in the Maasai Mara National Reserve, Kenya, may have resulted from the increased interactions of wildlife and livestock animals due to demographic pressures. Studies in Africa have documented brucellosis seroprevalence in African buffaloes ranging from 7.9% to 20.7% [ 20 , 21 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being reared separately, these herds mixed frequently during communal ceremonies. Studies have demonstrated that differences in livestock production and management systems may affect the spread of infections [46, 47].…”
Section: Discussionmentioning
confidence: 99%